Pengaruh Model Guided Discovery Learning Berbantuan Google Calssroom Terhadap Kemandirian Belajar Ekonomi Siswa Kelas XI IPS SMA Al-Islam 1 Surakarta - Esti Istina Wardani; Leny Noviani; Khresna Bayu Sangka (Jurnal Pendidikan Ekonomi (JUPE), 2023)
This study aims to determine the effect of the guided discovery learning model assisted by google classroom on student self reliance in economics learning at SMA Al-Islam 1 Surakarta academic year 2022. The research method is a quantitative quasi-experiment. The research subjects were 69 students of class XI IPS 1 and class XI IPS 2 SMA Al-Islam 1 Surakarta. The research sample was collected through a purposive sampling technique covering the criteria for the number of students in the same class, the conditions and abilities of the students were the same, and the class teachers were the same. Data collection using questionnaires, observation and documentation. The research data were analyzed using the independent sample t test with the result that the application of the guided discovery learning model assisted by google classroom had a positive and significant effect on student self reliance on economic learning.